O brincar e a criança com deficiência física na educação infantil : o que pensam as crianças e suas professoras - Lopes, Conceição Aparecida Oliveira (2012)
The present study had the purpose of examining the disabled children s way of playing on everyday situations in the CMEIs (acronym in Portuguese for City s Early Childhood Education Center ) of Natal/RN, by watching and listening to three children and their teachers, trying to understand how the games existent in these contexts involve the different subjects of the learning process, and which contributions emerge for a valuable pedagogic work, capable of providing the children s inclusion in the Early Childhood Education. This qualitative investigation was built as a case study, collecting data through watching and interviews. Throughout the observations, it was indispensable to look into the different contexts of the school routine, to capture and analyze events that could answer to what was being studied. The accessibility conditions of the school spaces were also observed. The interviews made possible to extract from the subjects what they think and how they perceive themselves when playing. The acquired data were analyzed having as counterparts contemporary studies and theories about playing, childhood and school inclusion, and published documents from the Education and Culture Department that treat of this theme as the guiding axis of the pedagogic proposes aimed to the Early Childhood Education. The revelations of the research show that is necessary to put effort on the disabled children s playing inside the context of the Early Childhood Education, regarding the accomplishment of accessibility laws that treat of school spaces and providing of equipment and resources that respect those children s characteristics, as well as providing opportunities for initial and continued training for the teachers, under the perspective of inclusive education and playing